2014
DOI: 10.3390/v6124926
|View full text |Cite
|
Sign up to set email alerts
|

“Ménage à Trois”: The Evolutionary Interplay between JSRV, enJSRVs and Domestic Sheep

Abstract: Sheep betaretroviruses represent a fascinating model to study the complex evolutionary interplay between host and pathogen in natural settings. In infected sheep, the exogenous and pathogenic Jaagsiekte sheep retrovirus (JSRV) coexists with a variety of highly related endogenous JSRVs, referred to as enJSRVs. During evolution, some of them were co-opted by the host as they fulfilled important biological functions, including placental development and protection against related exogenous retroviruses. In particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 91 publications
(176 reference statements)
2
49
0
Order By: Relevance
“…The development of such a defence mechanism was observed in sheep and koalas for example. Retroviral elements were endogenised even as recently as 200 and 100 years ago in the genomes of sheep and koala, respectively, providing protection against certain exogenous retroviral infections (Armezzani et al 2014;Tarlinton et al 2006).…”
Section: Shuttled Weaponsmentioning
confidence: 99%
“…The development of such a defence mechanism was observed in sheep and koalas for example. Retroviral elements were endogenised even as recently as 200 and 100 years ago in the genomes of sheep and koala, respectively, providing protection against certain exogenous retroviral infections (Armezzani et al 2014;Tarlinton et al 2006).…”
Section: Shuttled Weaponsmentioning
confidence: 99%
“…For instance, host endogenous envelope proteins may be produced and exported to the extracellular space by the host cells. These polypeptides will then compete for the host cell receptors with circulating viruses (JOHNSON, 2019 ;ARMEZZANI et al , 2014;ITO et al , 2013;ROBINSON et al , 1981) . The similarity of solo glycoprotein and glycoproteins from bona fide chuviruses and the Anakin retrovirus, as shown by sequence identity ( Supplementary Material 13 ) and comparison of three-dimensional structures ( Figure 4A ), indicates that some of these endogenous glycoproteins may play a role in antiviral defense mechanisms against circulating chuviruses or even against Anakin retroviruses through competition for cell receptors ( Figure 6 B ).…”
Section: Discussionmentioning
confidence: 99%
“…EVEs are normally found as fragments of exogenous viral genomes and it is therefore unlikely that they are able to generate new virus particles or infect new cells. Therefore, there are three main hypotheses regarding the fate and impact of these elements on the host genome: i) EVEs may evolve neutrally accumulating mutations and degenerate over time; ii) EVEs may be co-opted by the host genomes, giving rise to new functional host genes; and iii) EVEs may play an antiviral role, generating small RNAs which degrade cognate exogenous viral RNA or non-functional viral proteins that hinders proper assembly/maturation of a new viral particle or blocks the viral receptor on the host cell surface (ARMEZZANI et al , 2014;ITO et al , 2013;ROBINSON et al , 1981) . The vast majority of studies on EVEs found in mosquito genomes focus on the role of piRNA production as a post-transcriptional regulatory mechanism of exogenous circulating viruses (PALATINI et al , 2017;WHITFIELD et al , 2017 ;THÉRON et al , 2013) .…”
Section: Introductionmentioning
confidence: 99%
“…The research on these viruses has lead to important insights into the process of genome invasion by an ERV and of the changes that accompany endogenization (Anai et al, 2012;Arnaud et al, 2007a;Lavillette and Kabat, 2004;Li et al, 2012;Oliveira et al, 2007;Tarlinton et al, 2006). In koalas, sheep and cats and mice, exogenous counterparts of the respective ERVs are circulating in natural populations and are associated with disease (Armezzani et al, 2014;Kozak, 2015;Levy, 2008;Xu et al, 2015). Replication-competent variants of PERV have also been reported (Preuss et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…A practical classification is to consider ERVs as either "ancient" or "modern", based on the time when they infiltrated the host genome (Armezzani et al, 2014). Most ERVs belong to the ancient category, where the genome invasion occurred long time ago in the evolutionary history of the host species, usually before the last speciation.…”
Section: Introductionmentioning
confidence: 99%